2021
DOI: 10.2903/sp.efsa.2021.en-6925
|View full text |Cite
|
Sign up to set email alerts
|

Collection of data and information in Balearic Islands on biology of vectors and potential vectors of Xylella fastidiosa (GP/EFSA/ALPHA/017/01)

Abstract: The present document has been produced and adopted by the bodies identified above as authors. In accordance with Article 36 of Regulation (EC) No 178/2002, this task has been carried out exclusively by the authors in the context of a grant agreement between the European Food Safety Authority and the authors. The present document is published complying with the transparency principle to which the Authority is subject. It cannot be considered as an output adopted by the Authority. The European Food Safety Author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 42 publications
5
27
0
Order By: Relevance
“…As a result, further data on both host and vector infection during early stage spread for future pathogen incursions are urgently needed to verify these conclusions, especially given that studies in Spain have suggested that that there may be variability in the vector prevalence year on year 51 . We also note that there is some evidence that the prevalence amongst vectors declines towards the end of the year in Apulia 20 (and in other locations 51 ). We do not explicitly capture this decline in our model because the low numbers of vectors at this point (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, further data on both host and vector infection during early stage spread for future pathogen incursions are urgently needed to verify these conclusions, especially given that studies in Spain have suggested that that there may be variability in the vector prevalence year on year 51 . We also note that there is some evidence that the prevalence amongst vectors declines towards the end of the year in Apulia 20 (and in other locations 51 ). We do not explicitly capture this decline in our model because the low numbers of vectors at this point (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the abundance of nymphs and sampled adults as well as the prevalence of insects are lower than the values encountered in the infected areas of Apulia where the outbreak was more drastic. A prevalence of 23% was reported in Majorca (López-Mercadal et al 2021) compared to up to 71% detected in an Apulian olive grove (Cornara et al 2016a). Similarly, higher densities of vectors were measured in Apulia with 7 to 39 nymphs of P. spumarius /m 2 in olive orchards (Bodino et al 2019), about 7 adults/olive trees and 0.5 adults/swept in weeds recorded during the respective seasonal peaks (Cornara et al 2016b), however, with heterogeneity identified among the orchards studied (Bodino et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…multiplex ST81 and ST7) have been identified on several hosts including wild olives, cultivated olives, almonds, grapes and figs (Olmo et al 2021). They are mainly transmitted by the Philaenus spumarius Linnaeus, 1758 (Aphrophoridae) vector and to a lesser extent, by Neophilaenus campestris Fallén, 1805 (Aphrophoridae) (López-Mercadal et al 2021). This study experiments the sentinel plantation tool in the case of X. fastidiosa research.…”
Section: Introductionmentioning
confidence: 99%
“…As for the October 2020 transmission, the plants went into dormancy immediately afterwards and therefore, the period was less favorable for the subsequent bacterial development in the plants. However, October is a suitable month to collect infected insect vectors in Mallorca as it was shown that in general, prevalence was lower in summer months (June-July) compared to autumn ones (October), with an average of 23% (López-Mercadal et al, 2021). The X. fastidiosa prevalence found in field-collected insects in October 2020 was higher (16%) than the one found in June 2021 (5.2%) in accordance with the values commonly found in the area.…”
Section: Insect Transmission and Susceptibility To Different Strains ...mentioning
confidence: 99%